AKIBAT HUKUM TIDAK DIBAYARKAN PREMI ASURANSI JIWA OLEH PEMEGANG POLIS KEPADA PERUSAHAAN ASURANSI (KASUS MOLLY SITUWANDA DAN PERUSAHAAN ASURANSI JIWA PANIN DAI-ICHI LIFE) - Kenneth Kenneth; Mella Ismelina F.R. (Fakultas Hukum Universitas Tarumanagara, 2020)
In an insurance agreement, both the policyholder (the insured) or the insurance company (the insurer) have their respective rights and obligations which are contained in the insurance policy. The policyholder himself has the main obligation, namely to pay the premiums to the insurance company in accordance with the amount and time of payment specified in the insurance policy. If the policy holder is negligent in carrying out his obligations, it will cause his insurance policy status to enter into a lapse state. When the insurance policy goes into a lapse state, the policyholder has the potential to lose the rights that he should have received from the insurance program he participated in. This happened to Molly Situwanda as the beneficiary of her husband's life insurance policy, Astiang. This life insurance policy was issued by the Panin Dai-Ichi Life Life Insurance Company in 2010. In 2016, on December 28, 2016, to be precise, premium payments for Astiang's life insurance policy were no longer made by him, which resulted in the policy being entered into a lapse. However, at that time the investment / unit value was able to cover the premium costs up to October 15, 2018. After that date there were no more premium payments made by policyholders, which resulted in Astiang's life insurance policy going into lapse status or being inactive.